Stenotrophomonas Maltophilia and Urinary Tract Infections: A Systematic Review - Umar, Zaryab; Ashfaq, Salman; Parikh, Avish; Ilyas, Usman; Foster, Allison; Bhangal, Rubal; Khan, Jawad; Nassar, Mahmoud (Curēus (Palo Alto, CA), 2022)
Stenotrophomonas maltophilia, a gram-negative bacillus well known to cause respiratory tract infections, is increasingly being reported to cause urinary tract infections (UTI). In our review of the literature comprising six articles, males were more prone to developing UTIs, with the mean age of the patients being 62.5 ±18.9 years. While several risk factors have been associated with the development of the disease, patients with underlying urological or nephrological diseases tend to develop a more severe illness. The organism was sensitive to trimethoprim-sulfamethoxazole (TMP-SMX) in the majority of cases. This systematic review also aims to shed light on the possible mechanisms of resistance adopted by the bacteria, modes of transmission, and strategies to prevent the transmission and development of the disease.